2010
DOI: 10.1007/s10531-010-9915-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecological distribution of macrofungi in the Laojun Mountain region, southwestern China

Abstract: Surveys of the macrofungi associated with eight different vegetation types in the Laojun Mountain region of southwestern China yielded approximately 520 species belonging to 175 genera. Species richness and diversity were highest in mixed conifer and broadleaf forests and deciduous broadleaf forests. In typical forests of temperate regions of the world, there are five dominant genera of ectomycorrhizal macrofungi. The distribution patterns of species in these genera for the different vegetation types indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 64 publications
4
20
0
1
Order By: Relevance
“…Braga-Neto et al 2008;Durall et al 2006;Gates et al 2011a, b, c;McMullan-Fisher et al 2010;Sysouphanthong et al 2010). The turnover of species between habitats along environmental gradients is thought to be one of the dominant factors affecting macrofungal species richness at landscape scales (Braga-Neto et al 2008;Brown et al 2006;Lodge et al 1995;Nantel and Neumann 1992), and it has been demonstrated that environmental gradients related to altitude affect the diversity and distribution of macromycetes (O'Dell et al 1999;Zhang et al 2010). A literature review on species richness patterns showed that about half of the elevation gradient studies detected a mid-altitude peak in species richness (Rahbek 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Braga-Neto et al 2008;Durall et al 2006;Gates et al 2011a, b, c;McMullan-Fisher et al 2010;Sysouphanthong et al 2010). The turnover of species between habitats along environmental gradients is thought to be one of the dominant factors affecting macrofungal species richness at landscape scales (Braga-Neto et al 2008;Brown et al 2006;Lodge et al 1995;Nantel and Neumann 1992), and it has been demonstrated that environmental gradients related to altitude affect the diversity and distribution of macromycetes (O'Dell et al 1999;Zhang et al 2010). A literature review on species richness patterns showed that about half of the elevation gradient studies detected a mid-altitude peak in species richness (Rahbek 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation structure and plant species composition vary along environmental gradients, and this variation affects the macrofungal community and the presence of species associated to woody plants. The relationship between tree and fungal communities is reflected in host trees affecting fungal specialization and providing unique habitat availability and different resource quality (Villeneuve et al 1989;Lodge 1997;Ferrer and Gilbert 2003;Richard et al 2004;Brown et al 2006;Zhang et al 2010). Macromycete richness and distribution patterns have been related to the composition and structure of the tree community in temperate (Nantel and Neumann 1992;Gabel and Gabel 2007;Marmolejo and Méndez-Cortes 2007) and tropical habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Climatic and microclimatic conditions change with elevation; however, the changes of the diversity of macromycetes owing to elevation have been scarcely studied (Pouska et al 2010;Zhang et al 2010). Recent studies have concluded that precipitation (Lange 1978;Salerni et al 2002) or both humidity and temperature (Durall et al 2006) are the main factors related to macromycete fruiting.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of occurrence, H. cruenta is considered as very rare and rare species, recorded in the mountains more frequently than in uplands or lowlands (e.g., [5,23,32,36]). According to Parmasto [23], H. cruenta grows especially on the bark of various species of the genus Abies, and its occurrence on Picea is doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…Hymenochaete cruenta is a widespread fungus, known from Asia (China, Georgia, India, Japan, North Korea, Russia-Caucasus, and Turkey), South America (Argentina) and Europe (e.g., [23,24,32,[34][35][36]). In Europe, where its distribution is associated with the natural range of A. alba, H. cruenta has been announced to occur in Austria [23,37], Bulgaria [17], Croatia [38], the Czech Republic [9,23], France [23,39], Germany [40][41][42][43], Great Britain [44], the Macedonia Republic [45], the Netherlands [25], Italy [17,46], Romania [47,48], Russia [23], Slovakia [49], Slovenia [50], Spain [51,52], Switzerland [16], and Ukraine [5].…”
Section: Habitat and Distributionmentioning
confidence: 99%